Serum osteocalcin level in end-stage renal disease patients on maintenance hemodialysis after parathyroidectomy in relation to parathyroid hormone level - Soheir A Ellakany; Doaa I Hashaad; Alyaa F Merghany (SpringerOpen, 2019)
Background Parathyroidectomy (PTX) is an effective treatment for refractory hyperparathyroidism in end-stage renal disease (ESRD) patients on maintenance hemodialysis (MHD). However, adynamic bone disease, a possible complication, is associated with persistent bone pain and increased fracture risk. Osteocalcin (OC) is a bone formation marker, produced by osteoblasts, stimulated by parathyroid hormone and active vitamin D, associated with overall survival. Late changes in its level after PTX need to be evaluated. Aim The aim of this study was to determine serum OC and its relation to intact parathyroid hormone (iPTH) in patients on MHD with and without a history of PTX. Patients and methods This case-control study was conducted on 50 patients with ESRD on MHD, subdivided into two groups (group I and group II), according to the history of PTX. Patients having diabetic mellitus or autoimmune disease were excluded. Patients were inquired about manifestations of bone disease. Serum concentrations of ionized total calcium, magnesium, phosphorus, alkaline phosphatase (ALP), iPTH, and OC (by ELISA) were determined. Serum OC concentration was also measured in the samples of 20 healthy participants (group III) to evaluate its reference value. Results Bone fracture was present in nine patients with or without PTX, with no significant difference from the other patients, as regards the studied parameters. Patients with ESRD on MHD had a significantly higher serum OC level than controls (P<0.001). Serum OC in patients who underwent PTX, and with adynamic bone disease (iPTH<150 pg/ml) (group IA), was significantly lower than that in the corresponding subgroup without PTX (group 2A) (P=0.001); similarly, the two subgroups were different, as regards serum ALP (P<0.001) and serum iPTH (P<0.001). There were significant positive correlations between serum OC and total ALP and iPTH in the total patient sample (P<0.001 and <0.001, respectively). Conclusion Adynamic bone disease after PTX in patients on MHD in comparison with those who have not undergone PTX is associated with a lower level of bone formation marker OC.